Lipid peroxidation and sarcopenia: molecular mechanisms and potential therapeutic approaches - Lu, Yifan; Li, Tiao; Shu, Yang; Lu, Chengyin; Luo, Zhiqiang; Wang, Jingrui; Xiong, Hui; Li, Wangyang (Frontiers in Medicine, 2025)
Sarcopenia is an age-related condition characterized by the progressive loss of skeletal muscle mass and strength. With the global aging population, its incidence is rapidly increasing. Lipid peroxidation is a critical biochemical process that generates reactive oxygen species (ROS), leading to the destruction of muscle cell structure and function. It plays a pivotal role in the onset and progression of sarcopenia. This review summarizes the mechanisms by which lipid peroxidation contributes to sarcopenia, with a focus on its regulatory effects on cell membrane damage, mitochondrial dysfunction, and cell death. In addition, we discuss the protective role of antioxidant factors such as GPX4 (glutathione peroxidase 4) and antioxidant peptides like SS peptides in mitigating lipid peroxidation and delaying the progression of sarcopenia. Finally, the potential of various strategies, including natural compounds, supplements, natural extracts, and lifestyle interventions, in inhibiting lipid peroxidation and promoting muscle health is explored.